2017
DOI: 10.1038/s41598-017-03548-5
|View full text |Cite
|
Sign up to set email alerts
|

Label-free imaging of bone multiscale porosity and interfaces using third-harmonic generation microscopy

Abstract: Interfaces provide the structural basis of essential bone functions. In the hierarchical structure of bone tissue, heterogeneities such as porosity or boundaries are found at scales ranging from nanometers to millimeters, all of which contributing to macroscopic properties. To date, however, the complexity or limitations of currently used imaging methods restrict our understanding of this functional integration. Here we address this issue using label-free third-harmonic generation (THG) microscopy. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 65 publications
1
70
0
Order By: Relevance
“…Parallel collagen bundles in compact and trabecular bone elicit strong SHG signals. The signal intensities have been shown to directly correlate with the packing density and degree of fiber alignment . Areas of low collagen content, such as bone marrow cavities and osteocyte lacunae, remain dark (Fig.…”
Section: Label‐free Higher Harmonic Imaging Of the Bone Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…Parallel collagen bundles in compact and trabecular bone elicit strong SHG signals. The signal intensities have been shown to directly correlate with the packing density and degree of fiber alignment . Areas of low collagen content, such as bone marrow cavities and osteocyte lacunae, remain dark (Fig.…”
Section: Label‐free Higher Harmonic Imaging Of the Bone Matrixmentioning
confidence: 99%
“…Label‐free second and third harmonic generation (SHG/THG) microscopy has emerged as a powerful imaging approach to visualize the calcified and densely packed network of collagen fibers in the bone providing detailed information on the bone microarchitecture, endosteal surfaces, and the bone porosity . SHG signals result from the near‐simultaneous arrival of two photons at dense, noncentrosymmetric structures, such as collagen fibers.…”
Section: Label‐free Higher Harmonic Imaging Of the Bone Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen structures in SHG images have been analyzed in several publications [2,25,5,1,22,15,11]. They were analyzed in tissue [2] and bones [5,25]. Rao et al [15] presented how Fourier analysis can be used to investigate the orientation of collagen fibers.…”
Section: Related Workmentioning
confidence: 99%
“…Most recently, third‐harmonic generation (THG) has also been used for label‐free imaging in bone. In particular, THG can even image the star‐shaped osteocytes together with the porous lacuno‐canalicular network (LCN), which is a cellular level structure that reveals the geometry of osteocytes within bone matrices , as shown in Figure B . Tokarz et al showed that THG signal is mainly produced from the bone‐interstitial fluid boundary of the lacuna, while it is weaker from the interstitial fluid‐osteocyte boundary.…”
Section: Imaging Of Bone Matricesmentioning
confidence: 99%